128k views
3 votes
For all values of x, f(x)=x+5, g(x)=x²-2 Solve fg(x) = gf(x)


1 Answer

4 votes

Answer:

x=1

Explanation:

given-

f(x)=x+5

g(x)=x²-2

to solve,

fg(x)=gf(x)

so,

first of all let's put the values,

f(-2)=g(x+5)

x(-2)+5=(x+5)-2

-2x+5=+5x-2 (opened the bracket)

-x³-2x-5x+5+2=0(arranged the like terms)

-7x+7=0

-7x=-7{brought (+7) to RHS which is (-7)}

x=(-7)/(-7) [ (-7) was in multiplayer state by putting it in another side it changes into division state]

x = 1 { (-7)/(-7) divided by 1 and minus cancelled}

any confusion ask in CMT!!!

User Michael Dodd
by
5.2k points